Telstra’s Future Mode of Operation - the transformation of the Telstra’s Network - 1992/93 - Campbell, Ian (Journal of Telecommunications and the Digital Economy, 2017)
The Australian & Overseas Telecommunications Corporation (AOTC), later Telstra, was established on 1st January, 1992, as a government owned corporation and as the national telecommunications carrier. At the same time the Australian telecommunications market was deregulated and network competition was expected to begin within several months. Studies had indicated that AOTC’s inter-exchange network was perhaps five years behind similar networks in the USA and uncompetitive with the network to be built by the incoming competitor, Optus Communications (Optus). AOTC’s first Chief Executive Officer, Frank Blount, was an experienced senior executive of A&T, one of the most respected telecommunications businesses in the world, which had been operating in the highly competitive telecommunications market in the USA over the previous eight years. Blount decided that one of his highest priorities, if not the highest, was a major transformation of the AOTC’s inter-exchange network. Within seven months the AOTC board approved Plan D, an interim hybrid strategy which broadly achieved what was required for the network to be competitive. Within fourteen months the Board approved the Future Mode of Operation (FMO), a strategy to achieve a fully competitive, almost fully digital inter-exchange network which would approach world parity within five years. The FMO strategy would leap a gap close to ten years within five years. This is the story of the rationale and planning to launch Plan D and the FMO, the building of the first competitive telecommunications network strategy in the Postmaster General’s Department (PMG), Telecom Australia (Telecom) and AOTC (Telstra) in over 90 years.